1996
DOI: 10.1016/0014-5793(96)00693-x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of direction of uniform and accelerated visual motion and EEG alpha wave phases

Abstract: The perception of visual motion in seven subjects was studied comparing motion towards or away from the fixation point in the left or right hemifield. The light target was moved either at a constant velocity or positively or negatively accelerated to compensate for the magnification factor of the visual cortex. We compared probability and latency of motion recognition when it was asynchronous or synchronized to different phases of the alpha wave of the EEG recorded over the occipital cortex. If the motion acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Our findings also seem consistent with previous studies suggesting that alpha band oscillation is correlated with illusory perceptions in both visual and auditory modalities (Lenggenhager, Halje, & Blanke, 2011;Muller, et al, 2013;Shevelev, Kamenkovich, & Sharaev, 1996). For example, Lenggenhager et al beta rhythm has been shown in central brain areas (Keinrath, et al, 2006).…”
Section: Functional Ica Analysis In Eloretasupporting
confidence: 93%
“…Our findings also seem consistent with previous studies suggesting that alpha band oscillation is correlated with illusory perceptions in both visual and auditory modalities (Lenggenhager, Halje, & Blanke, 2011;Muller, et al, 2013;Shevelev, Kamenkovich, & Sharaev, 1996). For example, Lenggenhager et al beta rhythm has been shown in central brain areas (Keinrath, et al, 2006).…”
Section: Functional Ica Analysis In Eloretasupporting
confidence: 93%